Glutamatergic neurons of the paraventricular nucleus are critical contributors to the development of neurogenic hypertension. (20th September 2018) - Basting, Tyler; Xu, Jiaxi; Mukerjee, Snigdha; Epling, Joel; Fuchs, Robert; Sriramula, Srinivas; Lazartigues, Eric
Abstract : Key points: Recurrent periods of over‐excitation in the paraventricular nucleus (PVN) of the hypothalamus could contribute to chronic over‐activation of this nucleus and thus enhanced sympathetic drive. Stimulation of the PVN glutamatergic population utilizing channelrhodopsin‐2 leads to an immediate frequency‐dependent increase in baseline blood pressure. Partial lesions of glutamatergic neurons of the PVN (39.3%) result in an attenuated rise in blood pressure following Deoxycorticosterone acetate (DOCA)‐salt treatment and reduced index of sympathetic activity. These data suggest that stimulation of PVN glutamatergic neurons is sufficient to cause autonomic dysfunction and drive the increase in blood pressure during hypertension. Abstract: Neuro‐cardiovascular dysregulation leads to increased sympathetic activity and neurogenic hypertension. The paraventricular nucleus (PVN) of the hypothalamus is a key hub for blood pressure (BP) control, producing or relaying the increased sympathetic tone in hypertension. We hypothesize that increased central sympathetic drive is caused by chronic over‐excitation of glutamatergic PVN neurons. We tested how stimulation or lesioning of excitatory PVN neurons in conscious mice affects BP, baroreflex and sympathetic activity. Glutamatergic PVN neurons were unilaterally transduced with channelrhodopsin‐2 using an adeno‐associated virus (CamKII‐ChR2‐eYFP‐AAV2) in wildtype mice ( n  = 7) to assess the impact of acute stimulation of excitatory PVN neurons selectively on resting BP in conscious mice. Stimulation of the PVN glutamatergic population resulted in an immediate frequency‐dependent (2, 10 and 20 Hz) increase in BP from baseline by ∼9 mmHg at 20 Hz stimulation ( P  < 0.001). Additionally, in vGlut2‐cre mice glutamatergic neurons of the PVN were bilaterally lesioned utilizing a cre‐dependent caspase (AAV2‐flex‐taCASP3‐TEVp). Resting BP and urinary noradrenaline (norepinephrine) levels were then recorded in conscious mice before and after DOCA‐salt hypertension. Partial lesions of glutamatergic neurons of the PVN (39.3%, P  < 0.05) resulted in an attenuated rise in BP following DOCA‐salt treatment ( P  < 0.05 at 7 day time point, n  = 8). Noradrenaline levels as an index of sympathetic activity between the lesion and wildtype groups showed a significant reduction after DOCA‐salt treatment in the lesioned animals ( P  < 0.05). These experiments suggest that stimulation of PVN glutamatergic neurons is sufficient to cause autonomic dysfunction and drive the increase in BP. Key points: Recurrent periods of over‐excitation in the paraventricular nucleus (PVN) of the hypothalamus could contribute to chronic over‐activation of this nucleus and thus enhanced sympathetic drive. Stimulation of the PVN glutamatergic population utilizing channelrhodopsin‐2 leads to an immediate frequency‐dependent increase in baseline blood pressure. Partial lesions of glutamatergic neurons of the PVN (39.3%) result in an attenuated rise in blood pressure following Deoxycorticosterone acetate (DOCA)‐salt treatment and reduced index of sympathetic activity. These data suggest that stimulation of PVN glutamatergic neurons is sufficient to cause autonomic dysfunction and drive the increase in blood pressure during hypertension.